Effect of Oil Revenues on Government Size in Selected Oil-exporters with an Emphasis on Iran’s Economy - Jafari, Davood Danesh; Nazemian, Hamid; Bahrami, Javid; Kheiravar, Mohammad Hassan (International Journal of Energy Economics and Policy, 2020)
As a huge source of wealth, oil can serve as the engine of, or a barriers to, economic growth in oil-rich countries. The important issue is how to manage oil revenues while taking into account the welfare of future generations as a foundation of sustainable development. On the one hand, oil-exporters can lay the groundwork for sustainable development by allocating these revenues to infrastructural projects; on the other hand, they can create rents through corruption or mismanagement and thus create a strong barrier to the growth of macroeconomic indicators. Oil revenues have a significant role in Iran’s economy and are the main source of government expenditures. Oil accounts for the bulk of the country’s exports. One of the issues highlighted in Iran’s 2025 Vision is to cut the country’s dependence on oil revenues and finance spending through tax revenues, while allocating oil rents to efficient and productive investments. Therefore, the present research uses generalized method of moments (GMM) and autoregressive distributed lag (ARDL) to examines the effect of oil revenues on government expenditures and size in selected oil-exporting countries during 1980-2015 with an emphasis on Iran’s economy. The results suggest that oil revenues with one lag have a significant positive effect on government expenditures and size in the selected oil exporters. Moreover, In the case of Iran, increase in oil revenues has significant short-run and long-run effects on government size. Keywords: Oil Revenues; Government Size; GMM; Oil-Exporting Countries; Iran’s Economy JEL Classification: Q43 DOI: https://doi.org/10.32479/ijeep.10110